Highly Efficient Removal of Cadmium from Wastewater Using Eco-Friendly and Cost-Effective Amorphous Silicoaluminophosphates as Adsorbent Particles - Hamza Annath; Oluwafikayo Jaiyeola; Chirangano Mangwandi (Separations)
This article presents a study on the development of amorphous aluminophosphate (Am-AlP) and silico-aluminophosphate (Am-SiAlP) materials for the removal of cadmium (Cd) from wastewater. Cadmium is a toxic heavy metal that poses significant environmental and health risks, and its removal from water sources is crucial. This study explores the synthesis of these materials, focusing on the impact of silicon content on their adsorption properties. The materials were characterized using various techniques, including FTIR, XRD, TGA, and BET analysis, which revealed that the incorporation of silicon increased the surface area and porosity of the adsorbents, enhancing their cadmium removal efficiency. The Am-SiAlP (7.5) sample, with a 7.5 mol% Si content, showed the highest adsorption capacity (52.63 mg g−1) and removal efficiency (93%). Kinetic studies revealed that over 90% of cadmium was removed within the first 30 min, indicating rapid adsorption capabilities. The adsorption process was found to follow a pseudo-second-order kinetic model, indicating chemisorption as the rate-limiting step. The Langmuir isotherm model best described the adsorption, suggesting monolayer adsorption of cadmium on the adsorbent surface. This study also investigated the effect of interfering ions, showing that while the presence of other ions slightly reduced the adsorption efficiency, the Am-SiAlP (7.5) material still performed well. This research concludes that Am-SiAlP materials, particularly Am-SiAlP (7.5), are promising adsorbents for cadmium removal due to their high efficiency, cost-effectiveness, and environmental friendliness.